Whose Sins Do the Brethren Confess? The Problem of Sin as the Problem of Expiation. Issue 4 (8th August 2022) - Webster, Joseph
ABSTRACT: Among Brethren fisher-families in Gamrie, confession of sin is a private and pointedly interior affair. Yet, much of Brethren worship is given over to ritualised acts of confession. So whose sins do the Brethren confess? In Gamrie, such acts involve confessing not one's own sin, but the sins of 'fallen' world. By attending to the anthropological and theological processes of confessing the sins of another, we see a collapse in the distinction between confiteor and credo that has so dogged anthropological studies of Christianity . In Brethren prayer, bible study, and everyday gossip, the 'I confess' of the confiteor and the 'I believe' of credo co-constitute one another as evidences of the 'lostness' of 'this present age'. With the ritual gaze of confession turned radically outward, Brethren announcements of global wickedness enact (in a deliberate tautology) both a totalising call for repentance from sin, and a millenarian creed of the imminent apocalypse.